Primary scrotal lipoma in a child: a rare case report and review of literature - Meng Kong; Meng Kong; Yuexia Bai; Jinhua Jia; Jinhua Jia; Chuanyang Liu; Chuanyang Liu; Shisong Zhang; Shisong Zhang (Frontiers Media S.A., 2024)
Lipoma is a common benign tumor of the body surface, while scrotal lipoma is relatively rare. We report a case of scrotal lipoma in a 5-year-old boy, which presented as a progressively enlarging scrotal mass. Scrotal ultrasonography highly suggested a lipoma, and a scrotal mass resection was performed, leading to a final pathological diagnosis of benign scrotal lipoma.